Penentuan Nilai Opsi Saham Karyawan (OSK) dengan Memperhitungkan Efek Dilusi Menggunakan Metode Lattice Trinomial - Neneng Gusnela; Defri Ahmad (UNIVERSITAS NEGERI PADANG, 2020)
Abstract—Aim of this paper is to determine the value of Employee Stocks Options (ESO), in which the calculation is different with another options. This paper is based on literature study and example of the case is simulated by using computer software. Dilution effect that will causes a decrease in the stock value was also considered in this paper. Lattice trinomial method is used to modelling the stocks price movement. Based of the results of this paper, we obtain the value of ESO and observe the parameter effects. The influences of strike price, employee exit rate, and vesting time are inversely proportional to the value of ESO, while the interest rate and volatilitas are directly proportional to the value of ESO.Keywords—employee stocks options, dillution effect, lattice trinomial.